KNOWLEDGE, ATTITUDES AND BARRIERS TOWARDS PREVENTION OF MOTHER - TO - CHILD TRANSMISSION OF HIV IN GHANA - Mariwah, S.; Kumi-Kyereme, A.; Tanle, A.; Esia-Donkoh, K.; Owusu, S. A.; Atuahene, K. (UDS International Journal of Development, 2017)
While awareness of HIV and AIDS is near universal in Ghana, the same cannot be said of the prevention of mother-to-child transmission (PMTCT) of the disease. This paper assesses the level of knowledge, barriers and attitudes towards PMTCT of HIV/AIDS among pregnant women, partners of pregnant women and people living with HIV (PLHIV). Data were gathered through Focus Group Discussions (FGDs) and In-Depth Interviews (IDIs) from research participants purposively selected from cities/towns of the three ecological zones in Ghana. The inclusion criteria were border towns, commercial/mining towns/cities and towns/cities that have been known for high HIV/AIDS prevalence rates. The study found that most respondents were aware of MTCT but few knew about how it can be prevented. For pregnant women, the most prominent deterring factor is the fear of being diagnosed HIV positive and the associated stigma and discrimination. Therefore, creating community awareness on behaviours necessary to prevent MTCT is an essential step to improving participation, in and adherence to, PMTCT programmes. Keywords: Knowledge, Attitudes, PMTCT, HIV/AIDS, GhanaÂ